Development of single step pressure reduction system for natural gas vehicle. - Mohsin, Rahmat; Ashraf, Shameed; Abd. Majid, Zulkifli; Yaacob, Zulkifli; Hassan, Zulkafli; Ramlee, Mohd. Redhuan; Nasir, Abu Samah (Faculty of Chemical and Natural Resource Engineering, 2007)
The objective of this study is to design, fabricate and test a single step pressure regulation system for the natural gas motorcycle. The pressure regulator prototype design was based upon the fundamental principles of the pressure regulator. The aid of Computational Fluid Dynamic (CFD), pressure vessel code and threaded fastener standards were implied to design the pressure regulator prototype. The commercially available CFD code FLUENTTM was used to analyse and optimize the flow within the regulator. The structural design was based on the American Society of Mechanical Engineer (ASME) pressure vessel code. The Society of Automotive Engineers (SAE) and American Society of Testing and Materials (ASTM) served as reference for threaded fasteners selection. The material selection achieved for the prototype design consists of stainless steel 304, TeflonTM and 3 ply elastomer as the selected material of choice. The final CFD evaluation provided an optimum opening of 3 mm between the obturator and valve seat. The pressure regulator base has a wall thickness of 7.5 mm while the bonnet cap has 11.5 mm thickness. The loading element spring selected was a helical grounded type with 10 active coils and a wire diameter of 3 mm. The prototype designed was fabricated using Computer Numerical Configuration (CNC) machining as it is the best economically viable solution. The prototype performance was evaluated using the specially designed pressure regulator test bench equipped with data acquisition and high pressure gas supply system. Outlet gas flow rates were steadily controlled from 5 to 25 litres per minute and the outlet pressure was found to be steady at 4.5 bar. It is clearly proven that the developed pressure regulator is capable of providing the downstream components with natural gas at 4.5 bar up to 25 litres per minute. The single step pressure regulation developed, can be used on the Kriss Modenas 110cc or any small engines with similar fuel requirement.